Pengaruh Socio-cultural Influences dan Self-Compassion terhadap Apresiasi Tubuh Wanita: Social Appearance Comparison sebagai Mediator - Imanurul Aisha Rahardjo; Bagus Takwin; Imelda Ika Dian Oriza (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2021)
Self-image in general is an important part of humans. Having an ideal body shape according to the perceptions and norms that develop in society is usually a standard condition to be considered to be attractive. Self-image view is closely related to body image; mental picture of a person, cognitive and emotional assessments of himself, and approximately other people's judgments about the shape and size of his body. A positive body image is a multifaceted construct that is not simple so that it is not only a target of self-criticism but also an attitude of respect and self-acceptance which is called body appreciation. The purpose of this study was to find out the role of sociocultural influences and self-compassion on individual body appreciation and the presumption of the role of social appearance comparison variables as mediators between self-compassion and body appreciation. Participant were individuals aged 20-40 years consisting of 84 women. This research was conducted using multiple regression analysis. The results of the analysis, self-compassion contributed 21.7% to body appreciation and the proof of social appearance comparison mediated partially the relationship between self-compassion and body appreciation.